2020
DOI: 10.1109/emr.2020.3013206
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges and Opportunities in the Digitalization of Companies in a Post-COVID-19 World

Abstract: has caused dramatic effects on the world economy, business activities, and people. But digitization is also helping many companies to adapt and overcome the current situation caused by COVID-19. The growth in the use of technology in the daily lives of people and companies to face this exceptional situation is an evidence of the digital acceleration process. This exploratory study analyzes the impact of digital transformation processes in three business areas: labor and social relations, marketing and sales, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
214
0
17

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 383 publications
(238 citation statements)
references
References 17 publications
7
214
0
17
Order By: Relevance
“…In general, robots are expected to be progressively more autonomous, flexible, and cooperative in the post-pandemic world [ 135 ]. Regarding future research trends, the technologies underneath are suggested to enhance robotics research in the intra- and post-pandemic era: AI: AI is expected to be seen in almost every field from household applications to automated robot-assisted health services provided [ 136 ].…”
Section: Discussion and Identification Of Future Research Trendsmentioning
confidence: 99%
“…In general, robots are expected to be progressively more autonomous, flexible, and cooperative in the post-pandemic world [ 135 ]. Regarding future research trends, the technologies underneath are suggested to enhance robotics research in the intra- and post-pandemic era: AI: AI is expected to be seen in almost every field from household applications to automated robot-assisted health services provided [ 136 ].…”
Section: Discussion and Identification Of Future Research Trendsmentioning
confidence: 99%
“…Más personas interactuarán utilizando mecanismos de comunicación híbridos accesibles desde cualquier lugar y no exclusivamente en el entorno físico de las empresas y sus hogares. La ciberseguridad y la privacidad aparecen como elementos clave en la adopción de estas nuevas soluciones tecnológicas (Almeida et al, 2020).…”
Section: La Tecnologíaunclassified
“…La pandemia ha obligado a los gobiernos y a los responsables de la toma de decisiones a reevaluar cómo utilizan la información y extender el uso de la tecnología para mitigar muchos de los impactos sociales de la propagación del virus (Dwivedi et al, 2020). El enorme desafío para los gerentes es involucrarse en este cambio, mientras se intenta mantener el negocio en funcionamiento, frente a un futuro diferente e incierto (Almeida et al, 2020).…”
Section: La Tecnologíaunclassified
“…Siguiendo a Milgrom y Roberts (1992), puede concluirse que el desarrollo de las TIC permite gestionar de forma más eficiente los problemas de información y de coordinación de una organización, lo cual incide directamente en su adaptación al entorno competitivo. En el contexto actual, Almeida et al (2020) resaltan la importancia del papel que la digitalización puede ejercer en la competitividad de las empresas en la era pos-COVID-19. Y Fields et al (2020) observan que las prácticas de industria 4.0 han ayudado a mantener las actividades empresariales durante la crisis.…”
Section: Conclusiones Y Discusiónunclassified